POSTURAL DISORDERS REEDUCATION AT HEMIPARESIS PATIENTS WITH THE MBT PHYSIOTHERAPY DEVICE, EVALUATED USING BAROPODOMETRIC PLATFORM - Thaddeus Francisc Danelciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Postural control disorders represent one of the biggest problems in the recovery of CVA patients. Lately attention is given to posture maintaining analysis and mechanism of movement initiation. So postural control is another are where research and controversies are extremely numerous.